A large-scale, international cross-sectional survey of published pediatrics authors: Perceptions of complementary, alternative, and integrative medicine - Jeremy Y. Ng; Gursimran Deol; Dennis Anheyer; Holger Cramer (Elsevier, 2024)
Background: The use of complementary, alternative, and integrative medicine (CAIM) is commonly used among pediatric patients for various conditions. Pediatrics clinicians' and researchers' perceptions towards the incorporation of CAIM therapies have varied. This study aims to investigate the perceptions of both pediatrics researchers and clinicians regarding CAIM. Methods: We conducted a large-scale, international cross-sectional online survey with published pediatrics authors who have published their work in pediatrics medical journals that are indexed in MEDLINE. In total, 34 494 researchers and clinicians were invited to complete the survey. The survey recorded respondents' perceptions on various CAIM therapies. Descriptive statistics were generated from the quantitative survey results. A thematic analysis was conducted for responses to open ended questions. Results: In total, 731 pediatrics clinicians and/or researchers responded to the survey, with about half of the respondents being faculty members/principal investigators (56.10 %) and/or clinicians (43.45 %) and from the Americas (46.56 %) or Europe (30.53 %). Over half of the respondents viewed mind-body therapies favourably (62.01 %) and the fewest respondents held favourable perceptions of biofield therapies (6.98 %). Respondents agreed or strongly agreed that there is value in conducting further research on CAIM therapies (85.52 %) and disagreed or strongly disagreed that they felt comfortable recommending most CAIM therapies to patients (64.83 %). A thematic analysis of our findings demonstrates that many pediatrics clinicians and/or researchers support further research on CAIM. Conclusion: The findings from this study demonstrate that pediatrics clinicians and researchers have varying perceptions towards CAIM therapies. Respondents had the most positive perceptions of mind-body therapies and felt they did not have adequate training on CAIM. Further research is needed to establish more evidence-based educational resources on CAIM.